Are conservation agriculture (CA) systems productive and profitable options for smallholder farmers in different agro-ecoregions of Zimbabwe? - Mupangwa, W.; Mutenje, M.; Thierfelder, Christian L.; Nyagumbo, Isaiah (Cambridge University Press, 2017)
Continuous conventional tillage coupled with unsystematic cereal/legume rotations has promoted low crop productivity on smallholder farms. A multi-locational study was established in three agro-ecoregions (AEs) of Zimbabwe. The aim of the study was to determine the effect of four tillage systems (conventional plowing, planting basins, rip-line and animal traction direct seeding systems) on maize (Zea mays L.), cowpea [Vigna unguiculata (L.) Walp] and soybean [Glycine max (L.) Merrill] yields, and evaluate the economic performance of the conservation agriculture (CA) systems relative to conventional plowing. Each farmer was a replicate of the trial over the three cropping seasons. In the high (750–1000 mm per annum) and low (450–650 mm) rainfall AEs, conventional practice and CA systems gave similar maize grain yield. Under medium rainfall conditions (500–800 mm) planting basins, rip-line and direct seeding systems gave 547, 548 and 1690 kg ha−1 more maize yield than the conventional practice. In the high and low rainfall AEs, conventional practice and planting basins had the lowest maize production risk. Cowpea yield was 35 and 45% higher in the rip-line and direct seeding than conventional practice. Soybean yield was higher in rip-line (36%) and direct seeding (51%) systems than conventional practice. Direct seeding system gave the highest net benefits in all AEs. A combination of long-term biophysical and socio-economic assessments of the different cropping systems tested in our study is critical in order to fully understand their performance under different AEs of Zimbabwe.